Mastering research statistics - Chua, Yan Piaw (McGraw Hill Education, 2013)
This book is a practical guide that covers basic research statistics which can be used as teaching and learning tool for courses related to research at both undergraduate and post-graduate levels. This book will also prove invaluable to researchers. Concepts are explained in detail with examples to enable readers to carry out confidently each stage of the research process. Exercises are provided at the end of each chapter to help readers reinforce their understanding of the topics covered in the chapter.